Why Teach Mathematical Problem Solving - Ahmad Tarmizi, Rohani (Institute for Mathematical Research, 2008)
Problem solving is a basic skill needed by today's learners. Guided by recent research III mathematical problem solving, the changing professional standards, new workplace demands, technological changes and recent changes in learning theories, educators are to include integrated learning environments which encourage learners to use this higher order thinking skills, specifically problem solving skills. Teaching mathematical problem solving should take an approach of teaching in context where students are learning mathematics while solving realistic problems. Both holistic and componential opportunity modelings are approaches that have been emphasized in higher learning.